Probable neuropsychiatric toxicity of polyethylene glycol: roles of media, internet and the caregivers. Issue 3 (29th May 2019) - Hussain, Sunny Z.; Belkind‐Gerson, Jaime; Chogle, Ashish; Bhuiyan, Mohammad A. N.; Hicks, Timothy; Misra, Sudipta
Summary: Background and aim: To investigate the nature, origin and extent of reported neuropsychiatric side effects of polyethylene glycol 3350 (PEG, MiraLax © ) leading to avoidance of this laxative by parents and caregivers. Methods: We analysed (a) Federal Drug Administration (FDA) Adverse Effect Reporting System (AERS) data. (b) Google Search© and Google Trend© analysis of internet search trends of PEG side effects and (c) Surveys of US paediatric gastroenterologists. The data was analysed by descriptive statistics, chi squared tests with Benjamini‐Hochberg procedure. Results: Between 2007 and 2017, 1564 adverse symptoms (AS) were reported on 645 children between the ages of 0‐21. Of these, 919 (58.75%) were neurological, 770 of these were neuropsychiatric (83.8%), such as anxiety, anger, abnormal behaviour, etc. As media reports for AS were released, we found (a) a spike in internet traffic related to PEG AS and (b) a marked increase in AERS reporting; chronologically coinciding with release of media reports on AS. The internet activity has remained above the baseline since then. Of 149 paediatric gastroenterologists surveyed, 25 (16.8%) recalled neuropsychiatric symptoms reported by parents, PEG refusal was reported by 63.3% (76/120), significantly more by those reporting neuropsychiatric symptoms ( P  = 0.03). Conclusions: The PEG refusal reported by paediatric gastroenterologists was temporally related to an unprecedented and sustained spike of internet activity that immediately followed multiple media reports on PEG AS. It appears that negative public perception triggered by media reporting and amplified by internet activity has resulted in increased AERS reporting and parenteral refusal of PEG.